2015
DOI: 10.1590/1677-5449.0315
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre aplasia segmentar de veia safena magna e varizes em membros inferiores avaliada pelo ecocolor Doppler

Abstract: ResumoContextoHá diferenças individuais no diâmetro da veia safena magna (VSM) em membros normais e doentes; sendo possível a identificação dessas alterações pelo ecocolor Doppler.ObjetivoAvaliar a associação da aplasia segmentar da VSM com a presença de varizes e/ou insuficiência da mesma em membros inferiores, usando o ecocolor Doppler em pacientes com clínica de doença venosa crônica (DVC).Métodos1.408 pacientes com queixas compatíveis de DVC de membros inferiores, sendo 1.286 do sexo feminino, com idade en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Regarding the patient studied, partial lesion of the great saphenous vein was observed, which originates in the first toe, passing anteriorly through the internal malleolus, rising up the inner side of the leg, reaching the knee and performing internal ramifications until it united with the femoral vein 18 . Therefore, it can be concluded that this lesion originated from the stingray sting which, due to its sharp characteristics, grooves and jagged ends, allied to the region in which the sting was performed, showed exposure of the great saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the patient studied, partial lesion of the great saphenous vein was observed, which originates in the first toe, passing anteriorly through the internal malleolus, rising up the inner side of the leg, reaching the knee and performing internal ramifications until it united with the femoral vein 18 . Therefore, it can be concluded that this lesion originated from the stingray sting which, due to its sharp characteristics, grooves and jagged ends, allied to the region in which the sting was performed, showed exposure of the great saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
“…We have tried to classify the variants of hypoand aplastic GSV segment localization and extension according to the already known classifications. According to the classification of GSV aplasia described by Seidel A.C. et al (2012), there are 6 types of GSV aplasia: Type I -aplasia only in the thigh segment; Type II -aplasia in the tibial segment; Type III -aplasia in the distal segment of the thigh and the proximal segment of the tibia; Type IV -aplasia of the whole tibial segment; Type V -aplasia of the whole tibial segment and a significant part of the thigh segment without involving a short proximal segment; Type VI -aplasia of the entire vein without involving a short segment in the tibia [11,12]. According to the most common classification of GSV hypoplasia described by Caggiati A., Mendoza E. (2004), there are the following types of GSV hypoplasia: A -normally sized GSV segments join the suprafascial branch; B -distal GSV segment drains into the perforating vein; C -hypoplasia of the tibial part of the GSV; D -hypoplasia of the proximal part of the GSV which is shunted in the anterior accessory GSV [13].…”
Section: Discussionmentioning
confidence: 99%
“…Em uma amostra de 1408 pacientes, na qual foram examinados 2.665 membros inferiores, Seidel et al, 4 relatam aplasia de VSM em 61,8% no grupo sem varizes e em 38,2% dos membros com varizes. O resultado desse estudo mostrou que no grupo com varizes houve uma maior incidência de membros com associação de insuficiência e aplasia de VSM em relação ao grupo sem varizes.…”
Section: Discussionunclassified
“…A USV representa o principal método propedêutico na avaliação morfo-funcional das varizes dos membros inferiores, incluindo a VSM, sendo que a correta avaliação do sistema venoso através desse método é importante para o manejo da doença. 2 Embora estudos demonstrem uma associação entre a presença de variação anatômica e insuficiência da VSM, 2 outros estudos não corroboram tais achados, 3,4 tornando o tema ainda controverso.…”
Section: Introductionunclassified